PENDUGAAN BIOMASSA TEGAKAN JATI (TECTONA GRANDIS) DI HUTAN PENDIDIKAN DAN PELATIHAN SISIMENI SANAM - Yudhistira Ora; Fransiskus X. Dako; Jeriels Matatula (Politeknik Pertanian Negeri Kupang, 2013)
Biomass quantification of Teak (Tectona grandis) stands in Sisimeni Sanam Forestry Training and Education (SSFTE) center. Biomass quantification is an important step that needs to be understood and conducted in aclimate change activity or project from forestry sector. Method that commonly used in the biomass quantification is the allometric model. This study aims to arrange the allometric model of teak stand biomass in Sisimeni Sanam Forest. The sample trees are determined using uniform systematic distribution sampling method with sampling intensity 0.05%. The parameters measured are diameter and dry weight of the trees to determine the allometric model of the stands. The results of the study show that the allometric model of the teak stand biomass in Sisimeni Sanam Forest is Y = 0,32 X0,65. This model can be used to determined the whole biomass of the stand by just measuring the simple to measure atributes of trees such as the diameter.Keywords: Teak, Climate Change, Biomass, Allometric